The impact of forest naturalness and tree species composition on soil organic carbon content in areas with unnatural occurrence of Norway spruce in the Czech Republic - Marián Horváth; Petra Hanáková Bečvářová; Bořivoj Šarapatka; Václav Zouhar (Soil and Water Research, 2022)
Climate change has increased attention paid in the research to forest soils and tree species composition, in respect to the potential for carbon sequestration. It is known that forest stands are able to store soil organic carbon (SOC), but little is known about the effect of forest naturalness on SOC content. This is important in relation of dying of unnatural spruce stands. It is necessary to determine a suitable composition of tree species which will replace them. This research is based on 248 plots with oak, beech, and spruce stands and mixtures of these species, with measured values of SOC. Our results show that autochthonous and mixed stands, in terms of tree species composition, in the study area had a higher SOC content than allochthonous and pure stands. In addition, it was found that autochthonous oak and beech stands, especially in mixtures, had a higher SOC content than allochthonous spruce stands (monocultures). On the basis of the presented results, it is possible to optimize the future tree species composition of stands in the study area, which currently have an allochthonous representation of spruce, to provide better function of carbon sequestration and resistance to climate change.